Religious diversity, Islam, and integration in western Europe - dissecting symbolic, social, and institutional boundary dynamics - Koenig, Matthias (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
Religious diversity and, in particular, the presence of Islam is often perceived as a threat to national solidarity and social cohesion across Western Europe. Reviewing and synthesizing compartmentalized research literature on religion and immigrant integration, this article scrutinizes symbolic, social, and institutional boundary processes and their underlying micro-level mechanisms. First, it showcases the relative brightness of religiously coded symbolic boundaries that is sustained by anti-Muslim prejudices among the majority as well as by the intergenerational transmission of Muslim religiosity. Second, it discusses whether and how religious differences translate into social boundaries, through both discrimination and religiously based (self-)segregation on the labor market, in education, and in social networks. Third, it traces how interactive sequences of Muslims’ claims for recognition and public policy responses have led to institutional boundary shifts under the influence of constitutional law and European human rights and anti-discrimination directives. The article concludes by discussing scenarios of how macro-level processes of symbolic, social, and institutional boundary transformation interrelate, thus raising broader questions on religious diversity and integration in Western European nation-states.
Online veröffentlicht: 17. Oktober 2023
Gesehen am 18.12.2023
Zusammenfassung in deutscher Sprache